Hubungan Personal Hygiene dan Tingkat Aktivitas dengan Kejadian Scabies di Pondok Pesantren Putri Darussalam Blok Agung Banyuwangi - Faridatul Mukaromah , Luluk (CV. Ulil Albab Corp, 2024)
Scabies is a skin infestation caused by small mites called Sarcoptes scabiei. These mites create tunnels under the skin to lay eggs and live, causing the main symptom of intense itching, especially at night. Itching usually affects the skin folds, such as between the fingers, wrists, elbows, armpits, groin, buttocks and genitals. This study aims to determine the relationship between personal hygiene and activity level and the incidence of scabies at the Putri Darussalam Islamic Boarding School, Blok Agung Banyuwangi. This research uses a quantitative research design with a cross-sectional approach carried out at a certain time to collect data from research subjects. The sample in this research was female students from the Darussalam Block Agung Banyuwangi, totaling 30 respondents. Data collection was carried out using 3 types of questionnaires, namely questionnaires about personal hygiene, activity level and the incidence of scabies. Data analysis uses regression. Based on data analysis, the p value was <0.005, which means that personal hygiene and activity level are jointly related to the incidence of scabies.